Professional Swift - Dippery, Michael (Wrox programmer to programmer, 2015)
Professional Swift shows you how to create Mac and iPhone applications using Apple's new programming language. This code-intensive, practical guide walks you through Swift best practices as you learn the language, build an application, and refine it using advanced concepts and techniques. Organized for easy navigation, this book can be read end-to-end for a self-paced tutorial, or used as an on-demand desk reference as unfamiliar situations arise. The first section of the book guides you through the basics of Swift programming, with clear instruction on everything from writing code to storing data, and Section II adds advanced data types, advanced debugging, extending classes, and more. You'll learn everything you need to know to make the transition from Objective-C to Swift smooth and painless, so you can begin building faster, more secure apps than ever before.